2007
DOI: 10.1007/s10661-007-9673-7
|View full text |Cite
|
Sign up to set email alerts
|

Levels of polycyclic aromatic hydrocarbons and dibenzothiophenes in wetland sediments and aquatic insects in the oil sands area of Northeastern Alberta, Canada

Abstract: An immense volume of tailings and tailings water is accumulating in tailings ponds located on mine leases in the oil sands area of Alberta, Canada. Oil sands mining companies have proposed to use tailings- and tailings water-amended lakes and wetlands as part of their mine remediation plans. Polycyclic aromatic hydrocarbons (PAHs) are substances of concern in oil sands tailings and tailings water. In this study, we determined concentrations of PAHs in sediments, insect larvae and adult insects collected in or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 34 publications
2
79
1
Order By: Relevance
“…The pH of the tailings interstitial water underlying the Demonstration Pond ranged from 7.5 to 8.4. Alkalinity was not consistently measured at all sites; however, data estimated for the Demonstration Pond showed a corresponding increase in mean (standard error of the mean, n) alkalinity from 305 (6.0, 8) to 527 (1.5, 3) mg/L as CaCO 3 .…”
Section: Water Chemistry and Temperaturementioning
confidence: 80%
See 3 more Smart Citations
“…The pH of the tailings interstitial water underlying the Demonstration Pond ranged from 7.5 to 8.4. Alkalinity was not consistently measured at all sites; however, data estimated for the Demonstration Pond showed a corresponding increase in mean (standard error of the mean, n) alkalinity from 305 (6.0, 8) to 527 (1.5, 3) mg/L as CaCO 3 .…”
Section: Water Chemistry and Temperaturementioning
confidence: 80%
“…Thomas et al [28] also raised the possibility that PAHs can bind to androgen receptors. It is known that tailings porewater contained PAHs [2], and they were present in sediment and insects from the Demonstration and Bison Pond [3]. Furthermore, elevated levels of bile fluorescence, particularly at phenanthrene wavelength, and induced CYP1A enzyme activity in yellow perch in the Demonstration and Bison Ponds suggested that perch were being exposed to planar aromatic structures [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent assessment of PAHs in lakesediment cores provides compelling evidence that oil sands development has led to a significant increase in PAH levels in the AOSR environment (17). Although there have been studies providing insight into concentrations of PAHs in air (18), water (13), snow (13), sediments (10,17,(19)(20)(21), tailings pond pore water (22), and tailings pond sediments (10,21) in the AOSR, thorough characterization of PAH sources, pathways, and sinks within the AOSR is still lacking.…”
Section: Significancementioning
confidence: 99%